2019
DOI: 10.1587/elex.16.20190432
|View full text |Cite
|
Sign up to set email alerts
|

Power and thermal management in SRAM and DRAM using adaptive body biasing technique

Abstract: Low power and thermal design techniques are more advantageous for high-performance memory cells. Body bias is an adaptive technique used for power and thermal management in memory systems. It offers an efficient solution for the memory's power and thermal problems. In this study, a thermal management controller is presented as a complete hardware tuning loop. The controller is applied on both Static Random Access Memory (SRAM) and Dynamic Random Access Memory (DRAM) units that actively monitors and controls th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Thus, to estimate the overall power and thermal energy efficiency, it is necessary to guarantee that for a certain frequency, the dissipated power and temperature consumed will be minimum. Nano technologies introducing the gains in speed and higher power consumption of microprocessors and digital circuits, hence, the design of heatsinks is no longer been negligible that affecting performance as well as robustness of the cooling system (HamaAli et al, 2019). From microprocessors rigorous survey of power and thermal reduction in portable systems, it is observed that, there have been numerous articles, and published studies on the heatsink design and processor's power and thermal minimization techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, to estimate the overall power and thermal energy efficiency, it is necessary to guarantee that for a certain frequency, the dissipated power and temperature consumed will be minimum. Nano technologies introducing the gains in speed and higher power consumption of microprocessors and digital circuits, hence, the design of heatsinks is no longer been negligible that affecting performance as well as robustness of the cooling system (HamaAli et al, 2019). From microprocessors rigorous survey of power and thermal reduction in portable systems, it is observed that, there have been numerous articles, and published studies on the heatsink design and processor's power and thermal minimization techniques.…”
Section: Introductionmentioning
confidence: 99%